Management of deep neck infections in adults and importance of clinical and laboratory findings. (October 2022) - Arslan, Hande; Bayır, Ömer; Aksoy, Şevket; Keseroğlu, Kemal; Saka, Cem; Tatar, Emel Çadallı; Saylam, Güleser; Korkmaz, Mehmet Hakan
This study aimed to analyze laboratory and radiological imaging results in the prediction of treatment strategy in patients with deep neck infections. Eighty-three patients (55 (66.3%) men, mean age: 38.2±14.5 years) were included in the study. Patients were divided into three groups according to the treatment strategy: group 1 received only antibiotic treatment, group 2 underwent abscess drainage with needle puncture in addition to antibiotic treatment, and group 3 underwent surgical drainage with antibiotic treatment. Laboratory outcomes, imaging methods, duration of hospital stay, treatment strategy, and clinical outcomes were analyzed.According to the laboratory results, complete blood count values did not vary among the three groups, but C reactive protein (CRP) and erythrocyte sedimentation rate (ESR) values were higher in group 3 (p<0.01). Based on receiver operating characteristic (ROC) analysis, the cut-off levels for CRP and ESR associated with the need for surgical drainage were 133 mg/L and 42.5, respectively. According to radiological imaging results, the number of involved neck spaces was significantly different among the three groups (p=0.03), and group 3 had more spaces involved when compared with groups 1 and 2 (p=0.04). Gas formation in the neck tissues was noted in 10 patients in group 3 and 5 patients in groups 1 and 2 (p=0.02). ESR and CRP levels were higher in patients who underwent surgical drainage. In patients with deep neck space infections, the involvement of two or more neck spaces and gas formation on radiological images might indicate surgical drainage as a treatment strategy.